Insect Chitin-Based Nanomaterials for Innovative Cosmetics and Cosmeceuticals - Micaela Triunfo; Elena Tafi; Anna Guarnieri; Carmen Scieuzo; Thomas Hahn; Susanne Zibek; Rosanna Salvia; Patrizia Falabella (Cosmetics, 2021)
Chitin and its derivatives are attracting great interest in cosmetic and cosmeceutical fields, thanks to their antioxidant and antimicrobial properties, as well as their biocompatibility and biodegradability. The classical source of chitin, crustacean waste, is no longer sustainable and fungi, a possible alternative, have not been exploited at an industrial scale yet. On the contrary, the breeding of bioconverting insects, especially of the Diptera Hermetia illucens, is becoming increasingly popular worldwide. Therefore, their exoskeletons, consisting of chitin as a major component, represent a waste stream of facilities that could be exploited for many applications. Insect chitin, indeed, suggests its application in the same fields as the crustacean biopolymer, because of its comparable commercial characteristics. This review reports several cosmetic and cosmeceutical applications based on chitin and its derivatives. In this context, chitin nanofibers and nanofibrils, produced from crustacean waste, have proved to be excellent cosmeceutical active compounds and carriers of active ingredients in personal care. Consequently, the insect-based chitin, its derivatives and their complexes with hyaluronic acid and lignin, as well as with other chitin-derived compounds, may be considered a new appropriate potential polymer to be used in cosmetic and cosmeceutical fields.